Interstitial Cells of Blood Vessels - Vladimír Pucovský (The Scientific World Journal)
Blood vessels are made up of several distinct cell types. Although it was originally thought that the tunica media of blood vessels was composed of a homogeneous population of fully differentiated smooth muscle cells, more recent data suggest the existence of multiple smooth muscle cell subpopulations in the vascular wall. One of the cell types contributing to this heterogeneity is the novel, irregularly shaped, noncontractile cell with thin processes, termed interstitial cell, found in the tunica media of both veins and arteries. While the principal role of interstitial cells in veins seems to be pacemaking, the role of arterial interstitial cells is less clear. This review summarises the knowledge of the functional and structural properties of vascular interstitial cells accumulated so far, offers hypotheses on their physiological role, and proposes directions for future research.